2014
DOI: 10.1002/jnr.23477
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical circuitry mediating the sensory impact of nicotine in the central nervous system

Abstract: Direct actions of nicotine in the CNS appear to be essential for its reinforcing properties. However, activation of nicotinic acetylcholine receptors (nAChRs) on afferent sensory nerve fibers are important components of addiction to, and withdrawal from, cigarette smoking. The present study was to identify the neuroanatomical substrates activated by the peripheral actions of nicotine and to determine whether these sites overlap brain structures stimulated by direct actions of nicotine. Mouse brains were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 104 publications
(160 reference statements)
7
18
0
Order By: Relevance
“…A single acute injection of either nicotine or its peripherally-limited analog, nicotine pyrrolidine methiodide, have been observed to induce neural activity, confirmed through c-Fos immunoreactivity, in the RAIC but not the CGIC of mice [33]. Yet interestingly, the ␣7 subtype of the nicotinic acetylcholine receptor has been found within the CGIC but not the RAIC of rats [34].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A single acute injection of either nicotine or its peripherally-limited analog, nicotine pyrrolidine methiodide, have been observed to induce neural activity, confirmed through c-Fos immunoreactivity, in the RAIC but not the CGIC of mice [33]. Yet interestingly, the ␣7 subtype of the nicotinic acetylcholine receptor has been found within the CGIC but not the RAIC of rats [34].…”
Section: Discussionmentioning
confidence: 96%
“…As it receives afferents from the high-order [28] medial subdivision of the mediodorsal thalamic nucleus [29,30], along with those from multiple medial thalamic nuclei conveying motivational/affective aspects of peripheral stimuli, the RAIC is considered a high-order multimodal cortical region. The involvement of the RAIC has also been observed in certain models of nicotine addiction [16,31] and neural responses to nicotine exposure [32,33] in rodents.…”
Section: Introductionmentioning
confidence: 95%
“…The action of orexin in PVT has been implicated in the effects of nicotine on arousal and cognition and in nicotine addiction: peripheral nicotine administration increases Fos expression in orexin neurons projecting to PVT, as reported in the rat (Pasumarthi and Fadel, 2008), and increases of Fos expression in PVT neurons, as reported in the mouse (Dehkordi et al, 2014). Data in rat prefrontal cortical slices have shown that orexin and nicotine excite the same thalamocortical synapses (Lambe et al, 2005), pointing out a direct interaction of orexin and nicotine with thalamic midline terminals in the prefrontal cortex, besides their actions on PVT neurons.…”
Section: Orexinergic Innervation Of the Thalamusmentioning
confidence: 88%
“…The direct effects of nicotine on CNS neurons are critical for its reward and addiction properties [5-9]. Additionally, the sensory impacts of nicotine, mediated by exteroceptive and interoceptive sensory nerve endings in the gustatory, respiratory and circulatory systems, are important components of the nicotine reward-addiction circuitry [10-17]. The importance of the peripheral sensory impact of nicotine in its reward and addiction properties is documented in recent animal studies from our laboratory [17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the sensory impacts of nicotine, mediated by exteroceptive and interoceptive sensory nerve endings in the gustatory, respiratory and circulatory systems, are important components of the nicotine reward-addiction circuitry [10-17]. The importance of the peripheral sensory impact of nicotine in its reward and addiction properties is documented in recent animal studies from our laboratory [17]. We demonstrated that nicotine pyrrolidine methiodide (NIC-PM), a peripherally-acting analog of nicotine, that does not cross the blood brain barrier, activates virtually all the CNS sites that are direct targets of nicotine.…”
Section: Introductionmentioning
confidence: 99%